DESAIN DAN IMPLEMENTASI LAMPU RUANGAN OTOMATIS BERBASIS IoT - Siregar, Ivan Hengki; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2025)
Smart homes are part of an innovation in the application of the Internet Of Things, it can be seen that its application is able to automatically control almost all objects in the house. The purpose of the Internet Of Things (IoT) is continuously developed, one of which is to expand the use of the internet which is getting wider every day. With the development of technology and the existence of the Internet Of Things (IoT) which can be used in various fields of human needs today, for example with the existence of electronic room lighting devices that can be controlled remotely by utilizing an internet connection and controlled via an Android smartphone with a telegram application. In this study, a prototype of an automatic room lamp based on IoT was built, using the NodeMCU ESP8266 module as a microcontroller and to control remotely using the bot in the Telegram application. Based on the results of the trials carried out, it produced an IoT application that was able to control the lights from the telegram bot, so it can be concluded that the system can work well according to its objectives.